BREAST ANGIOSSARCOMA AFTER RADIOTHERAPY - Ramos, Leonor (2015)
Breast angiosarcoma is a rare tumor that can be divided in 3 groups: primary, secondary to chronic lymphoedema and secondary to radiotherapy (RT). It has a poor prognosis and a bad response to surgery and chemotherapy (QT). A female patient was observed with a very indurated erythematous-violaceous plaque, with an ecchymotic halo that occupied the right breast, and was evolving for 8 months. The patient had history of breast cancer, treated with surgery (tumourectomy) and local RT 5 years before. The incisional biopsy showed a vascular proliferation, arranged in nodules but also with diffuse growing, with cytological atypia and strong expression of CD31, CD34 and factor VIII, consistent with post-RT angiosarcoma. The patient begun RT and QT, but had no significant clinical response. She is now waiting for approval to begin pazopanib.